Tecnologias Waste-To-Energy: Conceito e Aplicação no Cenário Brasileiro de Gestão de Resíduos Sólidos Urbanos - Paratelli, Pedro Paulo Rodrigues [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
As population growth in urban areas is increasing, so is the consumption of goods and services, which increases waste generation. This growth coupled with the rise of sustainable agendas in international discussions and agreements pressures countries to adopt alternative ways to dispose of waste. This paper elucidates the main technologies for waste energy recovery, associating them as an alternative to the challenges and obstacles faced by the current Brazilian solid waste management plan, focusing on solutions that address environmental, social and governance (ESG) issues. Among the technologies presented, the one that presented the best balance between risk and efficiency was chosen, reaching the conclusion of the choice of the grate combustion technology. Afterwards, the economical aspects and key points necessary for the construction and operation of a Waste-To-Energy plant were presented, as well as the results obtained in a case study for the installation of a plant in the metropolitan area of Buenos Aires, Argentina. The analysis of these criteria made it possible to see the need for Brazil to adapt to the waste management hierarchy in a more judicious manner and established the steps to be taken so that the change to more modern and adequate MSW processing technologies may, in fact, be established on Brazilian territory.

Conforme o crescimento populacional em zonas urbanas está crescendo há também o crescimento do consumo de bens e serviços, o que aumenta a geração de resíduos. Esse crescimento somado a ascensão de pautas sustentáveis em discussões e acordos internacionais pressiona países a adotarem saídas alternativas para a destinação de resíduos. O presente trabalho elucida sobre as principais tecnologias de recuperação energética de resíduos associando as mesmas como uma alternativa aos desafios e obstáculos enfrentados pelo atual plano de gestão de resíduos sólidos brasileiro, focando em soluções que atendam questões ambientais, sociais e de governança (ESG). Dentre as tecnologias apresentadas, escolheu-se aquela que apresentasse o melhor balanço entre risco e eficiência, chegando à conclusão da escolha da tecnologia de combustão em grelha. Posteriormente foram apesentados os aspectos econômicos e pontos chaves necessários para construção e operação de uma planta Waste-To-Energy e os resultados obtidos em um estudo de caso para a instalação de uma planta na região metropolitana de Buenos Aires, Argentina. A análise desses critérios possibilitou enxergar a necessidade do Brasil em se adequar a hierarquia de gestão de resíduos de forma mais criteriosa e estabeleceu os passos a serem tomados para que a mudança para tecnologias de processamento de RSU mais modernas e adequadas sejam, de fato, estabelecidas em território brasileiro.
Waste-To-Energy Technologies: Concept and Application in the Brazilian Scenario of Municipal Solid Waste Management
Keywords: Environmental engineering; Recycling (Waste, etc.); Engenharia Ambiental; Gestão de Resíduos; Recuperação Energética